Disability Insurance and the Dynamics of the Incentive Insurance Trade-Off - Low, Hamish; Pistaferri, Luigi (American Economic Review, 2015)
We provide a life-cycle framework for comparing insurance and disincentive effects of disability benefits. The risks that individuals face and the parameters of the Disability Insurance (DI ) program are estimated from consumption, health, disability insurance, and wage data. We characterize the effects of disability insurance and study how policy reforms impact behavior and welfare. DI features high rejection rates of disabled applicants and some acceptance of healthy applicants. Despite worse incentives, welfare increases as programs become less strict or generosity increases. Disability insurance interacts with welfare programs: making unconditional means-tested programs more generous improves disability insurance targeting and increases welfare.